2016
DOI: 10.1038/srep38491
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a attenuates adipogenesis and promotes osteogenesis in steroid-induced rat BMSCs by targeting PPARγ and GREM1

Abstract: The imbalance between adipogenic and osteogenic differentiation in bone marrow mesenchymal stem cells (BMSCs) plays a significant role in the pathogenesis of steroid-induced osteonecrosis of the femoral head (ONFH). Several microRNAs (miRNAs) are involved in regulating adipogenesis and osteogenesis. In this study, we established a steroid-induced ONFH rat model to identify the potential relevant miRNAs. We identified 9 up-regulated and 28 down-regulated miRNAs in the ONFH rat model. Of these, miR-27a was down-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 43 publications
4
85
0
Order By: Relevance
“…Meanwhile, suppressed osteogenic activity has been detected in ONFH patients [15]. Restoration of osteogenic potential could alleviate the progression of ONFH in animal experiments [16]. Hence, we mainly focused on the rescue of ethanol-induced anti-osteogenic effects to reduce the development of alcohol-induced ONFH.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, suppressed osteogenic activity has been detected in ONFH patients [15]. Restoration of osteogenic potential could alleviate the progression of ONFH in animal experiments [16]. Hence, we mainly focused on the rescue of ethanol-induced anti-osteogenic effects to reduce the development of alcohol-induced ONFH.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Several recent studies also suggested that miRNAs might take part in the development of ONFH. [28][29][30] To date, alterations in circulating miRNAs in steroid-associated ONFH remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are 18-24 nucleotides, single-stranded, non-coding RNA. They have been proven to be involved in various tissues and biological functions [29]. For example, miR-141 and miR-200a have been reported to regulate osteoblast differentiation by targeting the BMP-2 signaling pathway [30].…”
Section: Discussionmentioning
confidence: 99%